A near-fatal case of intussusception and ischaemic perforation of stomach in first-trimester pregnancy: eight years after laparoscopic Roux-en-Y gastric bypass - Bhadra, Rajarshi (BMJ Case Rep, 2018)
The increasing demand and popularity of bariatric surgery are not only due to the ever-increasing obesity epidemic but to tackle obesity-related comorbidities like diabetes and hypertension. However, bariatric surgery is not free of complications. One rare complication is intussusception, jejuno-jejunal intussusception being the most common. Intussusception has been defined both in pregnant and in non-pregnant women as well as men. We describe the case of a 40-year-old woman in the first trimester of pregnancy came to the hospital with worsening abdominal pain, was found to have intussusception of small bowel involving the jejunum, along with ischaemic perforation and necrosis of the fundus of the stomach. Postsurgery, the patient had a complete recovery and eventually, she successfully delivered an intact, viable fetus.